2020
DOI: 10.2174/1381612826666200318130625
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P-gp in Glioblastoma: What we can Learn from Brain Development

Abstract: P-Glycoprotein (P-gp) is a 170-kDa transmembrane glycoprotein that works as an efflux pump and confers multidrug resistance (MDR) in normal tissues and tumors, including nervous tissues and brain tumors. In the developing telencephalon, the endothelial expression of P-gp, and the subcellular localization of the transporter at the luminal endothelial cell (EC) plasma membrane are early hallmarks of blood-brain barrier (BBB) differentiation and suggest a functional BBB activity that may complement the placental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 103 publications
1
16
0
Order By: Relevance
“…Among them, P-glycoprotein (ABCB1) is the most studied, and its role in the blood-brain-barrier is well-established [33]. Its increased expression and role in glioblastoma resistance have been reported [13,30,33,34] as well as its direct interaction with TMZ [35]. Our results demonstrated that besides MGMT, ABCB1 expression also increases in 3D glioblastoma cell culture more profoundly than in 2D.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Among them, P-glycoprotein (ABCB1) is the most studied, and its role in the blood-brain-barrier is well-established [33]. Its increased expression and role in glioblastoma resistance have been reported [13,30,33,34] as well as its direct interaction with TMZ [35]. Our results demonstrated that besides MGMT, ABCB1 expression also increases in 3D glioblastoma cell culture more profoundly than in 2D.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, the ATP-binding cassette (ABC) transporter superfamily plays an important role in glioblastoma resistance to chemotherapy [31,32]. Among them, P-glycoprotein (ABCB1) is the most studied, and its role in the blood-brain-barrier is well-established [33]. Its increased expression and role in glioblastoma resistance have been reported [13,30,33,34] as well as its direct interaction with TMZ [35].…”
Section: Discussionmentioning
confidence: 99%
“…P-Glycoprotein, referred to as multidrug resistance receptor (MDR1), is a transmembrane glycoprotein functioning as an efflux pump and conferring multidrug resistance in brain tumors 15 , 16 . We have previously reported high expression of MDR1 in GBM and demonstrated that down-regulation of MDR1 via Akt/NF-κB pathways upon transfection of the Ad-DKK3 gene augmented the anti-tumor effects of temozolomide in GBM cells and in a GBM-xenograft model 17 .…”
Section: Introductionmentioning
confidence: 99%
“…14 P-Glycoprotein, referred to as multidrug resistance receptor (MDR1), is a transmembrane glycoprotein functioning as an e ux pump and conferring multidrug resistance in brain tumors. 15,16 Elsewhere, we reported high expression of MDR1 in GBM and demonstrated that down-regulation of MDR1 via Akt/NF-kB pathways upon transfection of the Ad-DKK3 gene augmented the anti-tumor effects of temozolomide in GBM cells and in a GBM-xenograft model. 17 We also reported that a selective cyclooxygenase-2 (COX-2) inhibitor, celecoxib exerted anti-tumor effects associated with the down-regulation of Akt/NF-kB pathways in mouse glioma stem cells (GSCs) and GSCs-bearing glioma model.…”
Section: Read Full License Introductionmentioning
confidence: 87%